2020
DOI: 10.1186/s12866-020-01863-y
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoscorpion Wolbachia symbionts: diversity and evidence for a new supergroup S

Abstract: Background: Wolbachia are the most widely spread endosymbiotic bacteria, present in a wide variety of insects and two families of nematodes. As of now, however, relatively little genomic data has been available. The Wolbachia symbiont can be parasitic, as described for many arthropod systems, an obligate mutualist, as in filarial nematodes or a combination of both in some organisms. They are currently classified into 16 monophyletic lineage groups ("supergroups"). Although the nature of these symbioses remains… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 73 publications
1
36
0
1
Order By: Relevance
“…1 ), it is clear that multiple independent BOOM acquisitions have occurred in wolbachiae irrespective of lineage divergences. This is supported by a previous study positing recent BOOM acquisition in w Nfla and w Nleu ( Gerth & Bleidorn, 2017 ) and a current report that detected partial BOOM loci in w Apol, a Supergroup S Wolbachia strain infecting pseudoscorpions ( Lefoulon et al, 2020 ). The nature of BOOM flanking regions in the genomes of w CfeT, w VulC, w Cle, w Str, and w Lug, which collectively lack synteny and are riddled with transposases, recombinases and phage-related elements ( Table S3 ), also attests to LGT as the origin for BOOM in these genomes.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…1 ), it is clear that multiple independent BOOM acquisitions have occurred in wolbachiae irrespective of lineage divergences. This is supported by a previous study positing recent BOOM acquisition in w Nfla and w Nleu ( Gerth & Bleidorn, 2017 ) and a current report that detected partial BOOM loci in w Apol, a Supergroup S Wolbachia strain infecting pseudoscorpions ( Lefoulon et al, 2020 ). The nature of BOOM flanking regions in the genomes of w CfeT, w VulC, w Cle, w Str, and w Lug, which collectively lack synteny and are riddled with transposases, recombinases and phage-related elements ( Table S3 ), also attests to LGT as the origin for BOOM in these genomes.…”
Section: Resultssupporting
confidence: 88%
“…Some of the Wolbachia strains in closely related Supergroups C, F and D are considered mutualists with their nematode or arthropod hosts, supporting the absence of RP-inducing genes in the genomes of these strains. Still, other strains not included in our analysis, namely those belonging to Supergroups S ( Lefoulon et al, 2020 ; Chafee et al, 2010 ), P ( Glowska et al, 2015 ), and J ( Lefoulon et al, 2016 ) may eventually be shown to carry RP-inducing genes, especially since some of these strains are not known as mutualists. w Fol, another basal Wolbachia lineage ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the molecular characterizations of Wolbachia strains have been based on either single gene or multi-locus phylogenies [53, 55–65]. The supergroups A, B, E, H, I, K, M, N, O, P, Q and S are exclusively composed of symbionts of arthropods [55, 57, 59, 63, 66–70]. In contrast, supergroups C, D and J are restricted to filarial nematodes [4, 58, 61, 71], whereas supergroup L is found only in plant-parasitic nematodes [3, 72].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not known whether these functions are related to a particular Wolbachia strain or host [9]. As this bacterium has been found in association with hundreds of hosts and encompasses an immense diversity, the classification of strains into supergroups has been proposed and about 17 supergroups, to date, have been reported through genotyping a single gene, several genes, or even genomic approaches [10]. These supergroups are called "A to S", with G and R no longer considered separate supergroups [11,12].…”
Section: Introductionmentioning
confidence: 99%